X-ray spectral and timing evolution of MAXI J1727–203 with NICER. Issue 3 (6th August 2020) - Alabarta, K; Altamirano, D; Méndez, M; Cúneo, V A; Zhang, L; Remillard, R; Castro, A; Ludlam, R M; Steiner, J F; Enoto, T; Homan, J; Arzoumanian, Z; et al.
ABSTRACT: We present a detailed X-ray spectral and variability study of the full 2018 outburst of MAXI J1727–203 using NICER observations. The outburst lasted approximately four months. Spectral modelling in the 0.3–10 keV band shows the presence of both a soft thermal and a hard Comptonised component. The analysis of these components shows that MAXI J1727–203 evolved through the soft, intermediate, and hard spectral states during the outburst. We find that the soft (disc) component was detected throughout almost the entire outburst, with temperatures ranging from ∼0.4 keV, at the moment of maximum luminosity, to ∼0.1 keV near the end of the outburst. The power spectrum in the hard and intermediate states shows broad-band noise up to 20 Hz, with no evidence of quasi-periodic oscillations. We also study the rms spectra of the broad-band noise at 0.3−10 keV of this source. We find that the fractional rms increases with energy in most of the outburst except during the hard state, where the fractional rms remains approximately constant with energy. We also find that, below 3 keV, the fractional rms follows the same trend generally observed at energies >3 keV, a behaviour known from previous studies of black holes and neutron stars. The spectral and timing evolution of MAXI J1727–203, as parametrised by the hardness–intensity, hardness–rms, and rms–intensity diagrams, suggest that the system hosts a black hole, although we could not rule out a neutron star.